IMPROVING READING COMPREHENSION THROUGH FOLKLORE STORY AT MAN 1 PALU - ila Susani Pelo; Rasmi; Hijrah Syam (English Tadris Department, Faculty of Tarbiyah and Teacher Training, State Islamic University (UIN) Datokarama Palu, 2021)
This research aims to determine whether students’ reading comprehension can be improved by using the Folklore Story. The participants were 20 eleventh grade students. The researcher had carried out research during the pandemic, the number of students was limited by the school. The research employed true experimental and need pre-test and post-test to both experimental class and control class. The population of this research is students in the eleventh grade of Man 1 Palu. The students were selected randomly. They are 20 students of class XI MIA 1 as the experiment class and XI MIA 4 as a control class. The research analysed the data statistically data collection. The result of data analysis shows that the experimental class (86) is higher than the mean score of the control class (69). The deviation score of experimental class (8.75) is higher than of the control class (5.37). So, the result of t-counted (1.644) which is higher than t-table (0.081). in analyzing the data, the researcher used 0.05 level of significance and the degree of freedom (df=10+10-2) it means that the hypothesis of the research was accepted. Therefore, the Folklore Story can improve students’ reading comprehension.